2012
DOI: 10.1136/sextrans-2011-050454
|View full text |Cite
|
Sign up to set email alerts
|

Increasing chlamydia test of re-infection rates using SMS reminders and incentives

Abstract: Background Clients diagnosed and treated for Chlamydia trachomatis are a recognised high-risk group for subsequent infection. An estimated 8% of clients treated for chlamydia at Cairns Sexual Health Service return for re-testing within the recommended 3e4-month period. There is no recall or reminder system in place. This study assesses the effectiveness of using short messaging service (SMS) reminders with and without incentive payments to increase re-testing rates. Methods Eligible consenting clients were ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
66
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(77 citation statements)
references
References 16 publications
4
66
3
Order By: Relevance
“…Two trials reported statistically significant increases in testing for STIs. 17, 18 Lim et al 17 reported that mobile phone-based sexual health interventions can increase discussion of sexual health with a health-care professional threefold and lead to over a doubling of STI testing. Although some trial results look promising, the effects of text messaging on key safer sex behaviours, including telling your partner about your infection, correctly following treatment advice, obtaining STI testing for yourself and your partner(s) prior to unprotected sex and condom use, have not been reliably established.…”
Section: Fundingmentioning
confidence: 99%
See 2 more Smart Citations
“…Two trials reported statistically significant increases in testing for STIs. 17, 18 Lim et al 17 reported that mobile phone-based sexual health interventions can increase discussion of sexual health with a health-care professional threefold and lead to over a doubling of STI testing. Although some trial results look promising, the effects of text messaging on key safer sex behaviours, including telling your partner about your infection, correctly following treatment advice, obtaining STI testing for yourself and your partner(s) prior to unprotected sex and condom use, have not been reliably established.…”
Section: Fundingmentioning
confidence: 99%
“…The content was designed to address attitudes, information and behaviour skills, rather than induce fear, which has been found to be ineffective. 10,17,18 The formative work carried out with the target group on the development of the messages was key to the intervention's acceptability. Interviews were conducted shortly after participants had received the messages to minimise problems with recall.…”
Section: Strengths and Weaknesses Of The Qualitative Interviewsmentioning
confidence: 99%
See 1 more Smart Citation
“…Digital interventions for sexual health promotion may encourage people to use sexual health services, for example text messages to promote STI testing, 76,[85][86][87] to increase discussion of sexual health with a health-care professional 87 or to enhance the successful treatment of STIs. 88 Mobile phones and websites are also feasible ways to reach young people to encourage the use of condoms for safer sex.…”
Section: Digital Interventions For Sexual Health Promotionmentioning
confidence: 99%
“…At Cairns Sexual Health Service (CSHS), a generic SMS message with a small financial incentive increased chlamydia retesting from 7% to 28% 1. We implemented a client choice reminder system to determine if offering a choice would improve chlamydia retesting rates.…”
mentioning
confidence: 99%